First record of the Indo-Pacific red lionfish Pterois volitans (Linnaeus, 1758) in the Syrian marine waters (Banias). (Journal of Hama University, 2022)
A red lionfish, Pterois volitans (Linnaeus, 1758) (Osteichthyes: Scorpaenidae), was captured off Banias port and Arab almoulk area in the Syrian coast. This is the first record of the Indo-Pacific red lionfish P. volitans (Linnaeus, 1758) in Syrian marine waters. Six individuals were collected during September to November, 2020 at 10 m depth by fishing cages and spear fisherman. Lionfish are expected to target economically important fisheries, and coastal ecosystems appear to be under a new threat that may negatively affect local biodiversity.